Efektivitas Penagihan Pajak Dengan Surat Teguran Dan Surat Paksa Terhadap UMKM Dalam Pencairan Tunggakan Pajak - Agustin, Shintya; Kambuaya, Maylen K. P; Paru, Sara (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2024)
This research aims to see the effectiveness of tax collection with warning letters and forced letters against MSMEs in disbursing tax arrears. This research was conducted at KPP Pratama Jayapura. Data collection in this research used interviews conducted by one of the tax officials from the billing section and secondary data obtained from KPP Pratama Jayapura. This research uses a descriptive method with a quantitative approach. The sample used in this research is tax collection with warning letters and forced letters for 2018-2022. The data analysis technique is by using Effectiveness Ratio calculations and Descriptive Analysis using IBM Statistics 25. Based on the results of research using effectiveness ratio calculations, it shows that tax collection using warning letters and forced letters from 2018 to 2022 at KPP Pratama Jayapura is said to be ineffective. This is because the percentage rate of tax collection by warning letters or forced letters at KPP Pratama Jayapura is no more than 60%.